Nilai-Nilai Kepemimpinan Kepala Sekolah dalam Mengelola Organisasi Sekolah di SMK: Kajian Literatur - Novri Wahyuni; Ernawati Ernawati; Jonni Mardizal (Journal on Education, 2025)
This study discusses the leadership values ​​of principals in managing school organizations in vocational high schools. Principal leadership is a key factor in creating an effective learning environment and supporting the achievement of educational goals. Values ​​such as integrity, collaboration, strategic vision, ethics, and adaptability are the basis for principals in carrying out their roles as leaders. This study uses the literature review method to analyze various relevant studies on the influence of leadership values ​​on the management of school organizations in vocational high schools. The results of the study indicate that the application of these leadership values ​​has a positive impact on increasing teacher motivation, learning innovation, fair decision-making, and effective collaboration with stakeholders. These findings emphasize the importance of strengthening principal leadership values ​​in supporting strategic planning and improving the quality of education in vocational high schools. This study contributes to a deeper understanding of the relationship between principal leadership and successful school organization management.